2018
DOI: 10.1161/jaha.118.010395
|View full text |Cite
|
Sign up to set email alerts
|

Ascending Aorta Size at Birth Predicts White Matter Microstructure in Adolescents Who Underwent Fontan Palliation

Abstract: Background In neonates with single ventricle, smaller ascending aorta diameter is associated with cerebral white matter ( WM ) microstructural abnormalities. We sought to determine whether this association persists into adolescence. Methods and Results Ascending aorta Z scores were obtained from first postnatal echocardiogram. Brain magnetic resonance imaging with diffusion tensor imaging was acquired in adolescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The volumetric reductions in our dataset may reflect disruption to this highly orchestrated pattern and contribute to abnormal connectivity and cortical development detected in children/adolescents with CHD. 10,11,[34][35][36][37] Animal models and data from preterm neonates suggest that components of subplate, intermediate, and ventricular zones are vulnerable to hypoxia-ischemia. Hypoxia-ischemia alters the maturational trajectory and synaptogenesis of subplate neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The volumetric reductions in our dataset may reflect disruption to this highly orchestrated pattern and contribute to abnormal connectivity and cortical development detected in children/adolescents with CHD. 10,11,[34][35][36][37] Animal models and data from preterm neonates suggest that components of subplate, intermediate, and ventricular zones are vulnerable to hypoxia-ischemia. Hypoxia-ischemia alters the maturational trajectory and synaptogenesis of subplate neurons.…”
Section: Discussionmentioning
confidence: 99%
“…10 Remarkably, this association persists into adolescence. 11 Other factors operating in utero may also influence longterm brain structure, including deleterious gene variants, 12 placental dysfunction, 13 socioeconomic status, 14,15 and environmental exposures (eg, alcohol 16 ).…”
mentioning
confidence: 99%
“…There is evidence that microstructural changes are already evident at early life and may persist over time: white matter microstructure have been demonstrated in neonates with CHD (Hagmann et al., 2016; Karmacharya et al., 2018; Mulkey, 2014) and were associated with reduced functional connectivity in EEG (Birca et al., 2016). Zaidi and colleagues (Zaidi et al., 2018) demonstrated that the size of the aorta in neonates with a single ventricle heart defect predicted the anisotropy of the white matter microstructure in adolescents, suggesting a lasting influence of cerebral blood flow on white matter maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, alterations in WM microstructure and network topology have been found associated with neurodevelopmental disabilities and clinical risk factors. 10 , 11 , 12 , 13 , 14 , 15 Despite the importance of gray matter (GM) integrity in relation to neurocognitive abilities and motor skills, studies on the long‐term impact of CHD on microstructural GM development are lacking, probably due to methodological restrictions.…”
mentioning
confidence: 99%